A white garment of churches Romanesque and Gothic art - Adato, Perry Miller; WNET (Television station : New York, N.Y.).
Examines Romanesque and Gothic churches as evidence of the values of the societies that created them. Shows the effect of monasticism and pilgrimage on Romanesque church architecture. Uses Gislebertus's sculpture at St. Lazare in Autun to show the medieval focus on heaven and the afterlife. The Gothic architecture, sculpture, and stained glass at St. Denis and Chartres are discussed as evidence of a new theology and profound social changes during the twelfth and early thirteenth centuries.
An Annenberg/CPB project.
VHS.
Host, Michael Wood.
Keywords: Art, Romanesque; Art, Gothic